A Case of Bing–Neel Syndrome Successfully Treated with Ibrutinib - Daniel S. O’Neil; Mark A. Francescone; Karen Khan; Alobeid Bachir; Owen A. O’Connor; Ahmed Sawas (Case Reports in Hematology)
Bing–Neel syndrome is a rare manifestation of Waldenström macroglobulinemia characterized by lymphoplasmacytic cells’ infiltration into the central nervous system. We present a case of a 74-year-old patient with a known diagnosis of Waldenström macroglobulinemia and newly depressed consciousness. Flow cytology of his cerebral spinal fluid demonstrated a lambda light chain-restricted population of B-cells consistent with a CD5+ CD10+ B-cell lymphoma. Magnetic resonance imaging suggested involvement of the left optic nerve sheath and the bilateral orbital and parietal parenchyma and leptomeninges. He was diagnosed with Bing–Neel syndrome and treated with intrathecal liposomal cytarabine, intravenous high-dose methotrexate, and rituximab without improvement. Subsequently, he started treatment with ibrutinib 560 mg daily and concurrent rituximab. Within three months, he showed clinical and radiologic improvement. The patient has continued on ibrutinib and has now been stable for over 36 months. This represents the longest reported period of successful treatment of Bing–Neel syndrome with ibrutinib.